Experimental Study of the Nuclear Structure of 180Hf: Preliminary results - Vasileiou, Polytimos; Mertzimekis, Theo J.; Chalil, Achment; Zyriliou, Aikaterini; Pelonis, Stefanos; Lagaki, Varvara; Siltzovalis, Georgios; Efstathiou, Margarita; Koseoglu, Pavlos; Bonatsos, Dennis; Martinou, Andriana; Minkov, Nikolay; et al. (HNPS Advances in Nuclear Physics, 2022)
This work features preliminary results from a recent experimental campaign at IFIN-HH, Romania, aimed at measuring lifetimes of excited states in the neutron-rich 180Hf, by means of the RDDS technique. The 181Ta(11B,12C)180Hf proton pick-up reaction was used to populate excited states in the 180Hf nucleus. The ROSPHERE array loaded with 25 HPGe detectors was employed for the detection of the γ transitions depopulating the levels of interest. The array was coupled to the SORCERER particle detector and a plunger device enabling the study of p-γ and p-γ-γ coinciding events. Six different plunger foil distances were chosen, allowing for the construction of the decay curves of the observed γ transitions of interest, from which the corresponding level lifetimes can subsequently be deduced.